Dr. David A. Kim — Deep Plane Facelift — San Francisco - Kim, David A. (DEEPPLANE™, 2026)
Surgeon profile record for Dr. David A. Kim, practicing in San Francisco, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003134; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; san francisco